2022
DOI: 10.1007/s00704-022-03939-3
|View full text |Cite
|
Sign up to set email alerts
|

A new evolutionary time series model for streamflow forecasting in boreal lake-river systems

Abstract: Genetic programming (GP) is an evolutionary regression method that has received considerable interest to model hydro-environmental phenomena recently. Considering the sparseness of hydro-meteorological stations on northern areas, this study investigates the benefits and downfalls of univariate streamflow modeling at high latitudes using GP and seasonal autoregressive integrated moving average (SARIMA). Furthermore, a new evolutionary time series model, called GP-SARIMA, is introduced to enhance streamflow fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The observed errors suggest that SARIMA models tend to be more reliable for longer-term forecasts, in line with the findings of Alonso Brito et al [72]. Additionally, the performance of SARIMA models is highly sensitive to the training time series used in model calibration, as highlighted by Danandeh Mehr et al [35].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The observed errors suggest that SARIMA models tend to be more reliable for longer-term forecasts, in line with the findings of Alonso Brito et al [72]. Additionally, the performance of SARIMA models is highly sensitive to the training time series used in model calibration, as highlighted by Danandeh Mehr et al [35].…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, the SARIMA model only achieved a satisfactory rating at the 12 month forecast horizon. For instance, these findings differ from those of Danandeh Mehr et al [35,76] in their studies conducted for rivers in Turkey and Finland, whose NSE results with the SARIMA model report inferior to satisfactory performance in long-term forecasting. Similarly, the research of Chechi and Sanches [37] and Meis et al [77] observed the improved performance of SARIMAX to SARIMA in their studies for Brazilian watersheds, with their analyses highlighting the model's strengths in metrics like RMSE, NSE, and R 2 .…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Because of the need to assume linearity or heavy redundancy between lags, many optimal lag selection approaches underperform. To address the collinearity issue, this research also considered the average mutual information (AMI), which may be considered a nonlinear generalisation of the autocorrelation function [62]. The MI method is used in this research to select the best explanatory factors.…”
Section: Data Pre-processing Techniquesmentioning
confidence: 99%
“…In order to choose the most effective explanatory variables, the mutual information (MI) technique was applied in this study. Danandeh Mehr et al [52] stated that the average mutual information (AMI) is a non-linear generalization of the autocorrelation function. Mutual information is commonly utilized to locate time-delayed independent variables.…”
Section: Data Pre-processingmentioning
confidence: 99%